Actinobacillus pleuropneumoniae Surviving on Environmental Multi-Species Biofilms in Swine Farms - Loera-Muro, Abraham; Ramírez-Castillo, Flor Y.; Moreno-Flores, Adriana C.; Martin, Eduardo M.; Avelar-González, Francisco J.; Guerrero-Barrera, Alma L. (Frontiers in Veterinary Science, 2021)
Actinobacillus pleuropneumoniae is the etiologic agent of porcine contagious pleuropneumonia, an important respiratory disease for the pig industry. A. pleuropneumoniae has traditionally been considered an obligate pig pathogen. However, its presence in the environment is starting to be known. Here is reported the A. pleuropneumoniae surviving in biofilms in samples of drinking water of swine farms from Mexico. Fourteen farms were studied. Twenty samples were positive to A. pleuropneumoniae distributed on three different farms. The bacteria in the drinking water samples showed the ability to form biofilms in vitro. Likewise, A. pleuropneumoniae biofilms formation in situ was observed on farms drinkers where the biofilm formation displayed was in presence of other bacteria such as Escherichia coli, Stenotrophomonas maltophilia and Acinetobacter schindleri. Our data suggest that some strains of A. pleuropneumoniae survive in aquatic environments using multi-species biofilms as strategy to survive outside of its host.